Spectrophotometric Determination of Lanthanum (III) With Bromopyrogallol Red And Cetylpridinium Chloride -Applications in Natural Waters and Urine (Journal of Pharmaceutical Negative Results, 2022)
A highly sensitive spectrophotometric procedure for the estimation of lanthanum in aqueous medium has been established. The method was involved the reaction of lanthanum with bromopyrogallol as chelating agent in the presence of cetylpyridinium chloride at pH4.61 to produce a soluble blue colour ternary complex exhibited maximum absorption at 661nm. The method adheres to Beer's low over the concentration range 0.125 –5.0 μg/ml with coefficient determination (r2= 0.9987). The molar absorptivity(ℇ) of the ternary complex (La(III)-BPR-CPC) is 5.39x104 M-1cm-1 which corresponds to Sandell's sensitivity index of 0.00258 μg.cm-2. The stoichiometric composition of the ternary complex was estimated and found to be (1:2:4) (La:BPR:CPC), respectively. The values of detection limit (DL) and quantitation limit (QL) were calculated and found to be 0.0630 and 0.0817 μg.ml-1, respectively. A recovery% was found in the range 95.3% to 103.5%, while the precision (RSD) was estimated in the range 0.126 to 1.705. The proposed procedure has been applied successfully for the determination of lanthanum in natural waters and urine sample.